Basic Solutions for Managing Activities of Applying Information Technology in Teaching English in High Schools in Ho Chi Minh City Under Comprehensive Quality Management Approach - Thi, Phuong - Kim Nguyen; Thi, Thuy - Chau Cao (International Journal of Membrane Science and Technology, 2023)
After 37 years of innovation, integration and development, Vietnam has achieved many great achievements, with its position and strength becoming stronger than ever. Economic development, political and social stability; Culture and society have developed, national defense and security have been strengthened; The material and spiritual life of the people is increasingly improved. Also in that process of innovation and integration, Vietnamese education has achieved many achievements in improving the quality of human resources and promoting the human factor to promote the country’s development. With the efforts of administrators and teachers, the management of information technology application activities in English teaching in high schools has initially had positive changes in a number of aspects. This study was conducted to analyze and clarify basic solutions for managing information technology application activities in English teaching in high schools in Ho Chi Minh City according to the total quality management approach aspect - TQM (Total Qualityl Management). The results show that managing information technology application activities in English teaching according to the Total Quality Management model will contribute to ensuring that technology is being used effectively in schools learning, promoting and facilitating the effective application of information technology to teachers’ teaching activities and students’ learning activities, contributing to improving the quality of teaching. The basic solutions that the article states and analyzes towards managing the application of information technology to English teaching in high schools in Ho Chi Minh City are: raising awareness for officials and teachers. lecturer on the importance of applying information technology to teaching English in high schools according to the Total Quality Management approach; stage control of the management process of applying information technology to English teaching according to the Total Quality Management approach; Implement a quality management system for applying information technology to English teaching according to the Total Quality Management approach in schools. The limitation of this study is that it has not stated and analyzed the factors that affect the management of information technology application activities in teaching English in high schools in Ho Chi Minh City according to the approach comprehensive quality management.